A new approach for modeling dry deposition velocity of particles. (May 2018) - Giardina, M.; Buffa, P.
Abstract: The dry deposition process is recognized as an important pathway among the various removal processes of pollutants in the atmosphere. In this field, there are several models reported in the literature useful to predict the dry deposition velocity of particles of different diameters but many of them are not capable of representing dry deposition phenomena for several categories of pollutants and deposition surfaces. Moreover, their applications is valid for specific conditions and if the data in that application meet all of the assumptions required of the data used to define the model. In this paper a new dry deposition velocity model based on an electrical analogy schema is proposed to overcome the above issues. The dry deposition velocity is evaluated by assuming that the resistances that affect the particle flux in the Quasi-Laminar Sub-layers can be combined to take into account local features of the mutual influence of inertial impact processes and the turbulent one. Comparisons with the experimental data from literature indicate that the proposed model allows to capture with good agreement the main dry deposition phenomena for the examined environmental conditions and deposition surfaces to be determined. The proposed approach could be easily implemented within atmospheric dispersion modeling codes and efficiently addressing different deposition surfaces for several particle pollution. Highlights: Dry deposition process is an important pathway to remove pollutants in atmosphere. A new dry deposition velocity model based on electrical analogy schema is proposed. The model can be applied for different deposition surfaces. This approach can easily implemented in atmospheric dispersion modeling codes.